Deep brain stimulation in early stage Parkinson's disease: operative experience from a prospective randomised clinical trial. Issue 2 (2nd September 2011) - Kahn, Elyne; D'Haese, Pierre-Francois; Dawant, Benoit; Allen, Laura; Kao, Chris; Charles, P David; Konrad, Peter
Abstract : Background: Recent evidence suggests that deep brain stimulation of the subthalamic nucleus (STN-DBS) may have a disease modifying effect in early Parkinson's disease (PD). A randomised, prospective study is underway to determine whether STN-DBS in early PD is safe and tolerable. Objectives/methods: 15 of 30 early PD patients were randomised to receive STN-DBS implants in an institutional review board approved protocol. Operative technique, location of DBS leads and perioperative adverse events are reported. Active contact used for stimulation in these patients was compared with 47 advanced PD patients undergoing an identical procedure by the same surgeon. Results: 14 of the 15 patients did not sustain any long term (>3 months) complications from the surgery. One subject suffered a stroke resulting in mild cognitive changes and slight right arm and face weakness. The average optimal contact used in symptomatic treatment of early PD patients was: anterior −1.1±1.7 mm, lateral 10.7±1.7 mm and superior −3.3±2.5 mm (anterior and posterior commissure coordinates). This location is statistically no different (0.77 mm, p>0.05) than the optimal contact used in the treatment of 47 advanced PD patients. Conclusions: The perioperative adverse events in this trial of subjects with early stage PD are comparable with those reported for STN-DBS in advanced PD. The active contact position used in early PD is not significantly different from that used in late stage disease. This is the first report of the operative experience from a randomised, surgical versus best medical therapy trial for the early treatment of PD.